MODEL PRACTICE OF PEDAGOGICAL REASONING AND ACTION TEACHING IN THE SECONDARY SCHOOL PHYSICAL EDUCATION TEACHERS IN SELANGOR - Mat Som, Mohamed Faizul (EARR (Educational Administration Research and Review), 2022)
This study aims to determine the extent of the practice using a survey method in questionnaires, with 580 samples taken from the teachers who teach physical education subjects. This study determines the degree of correspondence model of reasoning practice pedagogy, focusing on dimensions of understanding, transformation and teaching as eksogen variable. While on the other hand dimension of evaluation, reflection and understanding a new is practice action teaching teachers as endogen variable. This study uses the Structural Equation Modeling analysis method (SEM), where the findings explain the testing Goodness of Fit Chi Square with degrees of freedom which is 53, CMIN/DF 111.298 is 2.100 (5), Comparative Fit Index (CFI) ialah .993 ( . 90), Tucker Lewis Index (TLI) is 989. (. 90. While the Root Mean Square Error of Approximation (RMSEA) value at .044 (0.05). The measurement of the model this study proves that is able to match with the data model of a good review. The findings of the study significant the practice impresses determination between pedagogical reasoning and the act of teaching physical education among teachers in the model equation structure. This correlates with the actual teaching phenomenon that is happening in the secondary school in Selangor.